2008
DOI: 10.4314/ajtcam.v5i1.31258
|View full text |Cite
|
Sign up to set email alerts
|

<i>In vitro</i> antioxidant activities of the fractions of </i>Coccinia grandis</i> l. leaf extract

Abstract: The present study was aimed at investigating the antioxidant activities of the various fractions of the hydromethanolic extract of the leaves of Coccinia grandis L. Voigt. (Cucurbitaceae). The antioxidant activities of the fractions have been evaluated by using nine in vitro assays and were compared to standard antioxidants such as ascorbic acid, α-tocopherol, curcumin and butylated hydroxyl toluene (BHT). All the fractions showed effective Hdonor activity, reducing power, free radical scavenging activity, met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
194
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(199 citation statements)
references
References 35 publications
5
194
0
Order By: Relevance
“…Umamaheswari and Chatterjee analyzed in vitro varied antioxidant of the different solvent fractions of Coccinia grandis leaf extracts. 21 The present AOX potential of Osbeckia species are comparable with the above results. Purified anthocyanin of both the species showed remarkable activity ie 68.5 and 63.4 percentage respectively at 25 µg/ml (Table 4).…”
Section: Hydroxyl Radical ( -Oh) Scavenging Activitysupporting
confidence: 79%
See 1 more Smart Citation
“…Umamaheswari and Chatterjee analyzed in vitro varied antioxidant of the different solvent fractions of Coccinia grandis leaf extracts. 21 The present AOX potential of Osbeckia species are comparable with the above results. Purified anthocyanin of both the species showed remarkable activity ie 68.5 and 63.4 percentage respectively at 25 µg/ml (Table 4).…”
Section: Hydroxyl Radical ( -Oh) Scavenging Activitysupporting
confidence: 79%
“…20 Umamaheswari and Chatterjee analyzed in vitro antioxidant activities of the fractions of Coccinia grandis leaf extract. 21 Saito et al extensively activity is dependent on the chemistry of anthocyanins and not all of them show similar activities for scavenging ROS and RNS. The antioxidant ability of anthocyanins depends on the basic structural orientation of the compound because the ring orientation will decide the way by which a hydrogen atom from a hydroxyl group can be donated to a free radical as well as the potentiality of the anthocyanin to support an unpaired electron.…”
Section: Discussionmentioning
confidence: 99%
“…In plants reducing power assay has been considered as one of the most important indicator of antioxidant activity. 49 The presence of reductones in the plant extract is commonly correlated with its reducing capabilities as reductones have shown the antioxidant action by terminating the radical chain reaction as they donates hydrogen atom in the reaction mixture. 50 In our study, it has been observed that the total reduction ability of converting Fe 3+ to Fe 2+ in presence of both the extracts increases in a concentration dependent manner suggesting that both the extracts donates an electron in the reaction mixture which reacts with free radicals breaking down the chain reaction and transform them into much stable non-radical products.…”
Section: Total Reducing Powermentioning
confidence: 99%
“…Antioxidants fight against free radicals and defend us from various diseases. They exert their action either by scavenging the reactive oxygen species or protecting the antioxidant defense mechanisms 28 . The electron donation ability of natural products can be measured by 2, 20 -diphenyl -1 -picryl hydrazyl radical (DPPH) purple-coloured solution bleaching 9 .…”
Section: Fig 2: Abts (Total Antioidant Activity) Free Radical Scavenmentioning
confidence: 99%